A Review on Pancreatic Lipase Inhibitors from Natural Sources: A Potential Target for Obesity - T, Bency B.; R, Murali; TNK, Suriyaprakash; N, Srinivasan (Current Enzyme Inhibition, 2021)
Background: Obesity is a worldwide lifestyle disorder and its incidence is growing at an alarming rate. Pancreatic lipase (PL) plays a key role in lipid metabolism and hence is a potential target for obesity treatment. There have been reports that many bioactive compounds from natural sources constitute a vast pool of PL inhibitors. Objective: In search of natural pancreatic lipase inhibitors, the review summarizes the potential of natural products for their pancreatic lipase inhibitory activity. Methods: In this review, the data obtained from literature search of various electronic databases and journal article publications have been reviewed. Results: The pancreatic lipase inhibitory activities of 61 biological sources reviewed in this paper are backed by preclinical experimental evidence, either in vivo or in vitro. Conclusion: This article can be used as a ready-to-use reference for therapeutic lead molecules from plants, marine and insect-derived natural products with PL inhibitory activity. The research is more focused on the discovery of more ingenious pancreatic lipase inhibitors with lesser consequences.
Keywords: Pancreatic lipase